Evaluasi Strategi Komunikasi Konselor BP4 dalam Mencegah Perceraian - Yenni Sri Utami (CHANNEL: Jurnal Komunikasi, 2015)
The divorce rate in the of Yogyakarta city also increased in this two last years, while the KUA strives to improve the quality of marriage according teaching of islamic.through counseling and marriage counseling continuously and consistently. It is inteded that can to realize home stairs that harmonious. BP4 (Badan Penasihat Pembinaan dan Pelestarian Perkawinan) through counseling and mediation serve consultations marriage against the family problematic. The Capacity of communicating a BP4 counselors play an important role in carrying out its duties to prevent divorce. This reasearch was conducted to evaluate the communication strategy executed BP4 counselors Mergangsan District of Yogyakarta in preventing divorce. Through research kualitatif with approaches to case study (studi kasus) is used to solve the existing problems in this study. The results of the research showed that the BP4 as a semi-official agency under the coordination KUA role in mediating and preventing divorce is merely to help resolve the problems faced by married couples who disagree so peaceful. However, in practice communication BP4 less able to function properly to prevent divorce. This is due to personal ability BP4 who do not have the ability as a mediator. The counselor BP4 at KUA Mergangsan district of Yogyakarta besides there is only one person, and even then did not have the educational background of competent, well in carrying out its duties do not have a Standard Operating Procedure (SOP) a counselor. Thus the need for reform and improvement of the quality of existence BP4 counselors at KUA Mergangsan district of Yogyakarta since there are many who need it.Key words: Marriage, KUA, Counseling.